Pengaruh Return On Asset Dan Debt To Equity Ratio terhadap Dividen Payout Ratio pada Perusahaan Sektor Basic Materials yang Terdaftar di BEI Periode 2018-2023 - Viola Nur Lita; Mirza Anindya Pangestika (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This is research purpose to analyze the influence of Return On Assets (ROA) and Debt To Equity Ratio (DER) on the Dividen Payout Ratio (DPR) in manufacturing companies in the basic materials sector listed on the Indonesian stock exchange for the 2018-2023 period. This research uses quantitative methods. The population and sample in ithis research are the annual financial reports of companies in the basic materials sector for the 2018-2023 period. The sample in the study was 54 financial reports taken using purposive sampling techniques. The data analysis used in this research is multiple linear regression analysis using the SPSS 22 application. The results of the research show that partially Return On Assets and Debt To Equity Ratio have a significant effect on the Dividen Payout Ratio. Simultaneously Return On Assets and Debt To Equity Ratio have a significant on the Dividen Payout Ratio.